Draft Eighth Five Year Plan (1990-95) and Annual Plan 1991-92 Government of Arunachal Pradesh - Planning Commission (Planning Commission, 1990)
The main thrust of the 7th Plan strategy, has been for the development of infrastructural facilities. Agriculture and Allied Services, Power and Transport & Communication Sectors were the priority sectors. Adequate attention was, however, given to the social services to improve the quality of life.
Government of Arunachal Pradesh, Planning and Development Department